Effects of repetitive transcranial magnetic stimulation on sequelae in patients with chronic stroke: A systematic review and meta-analysis of randomized controlled trials - Chen, Gengbin; Wu, Manfeng; Lin, Tuo; Cai, Guiyuan; Xu, Jiayue; Ding, Qian; Li, Wanqi; Wu, Cheng; Chen, Hongying; Lan, Yue (Frontiers in Neuroscience, 2022)
Abstract Background: Stroke is the second leading cause of death worldwide, with a large proportion of survivors suffering from motor dysfunction and neuropsychiatric sequelae. Repetitive transcranial magnetic stimulation (rTMS) is a promising stroke rehabilitation intervention and is effective in improving neurological system function in stroke patients. In the current systemic review and meta-analysis, an overview of the most recent studies regarding the effectiveness of rTMS’s potential to help chronic stroke patients recover from sequelae was provided. Methods: Relevant randomized controlled trials were retrieved from three online databases (Web of Science, Medline, and Embase). A total of 25 RCTs (N=535 participants) were included. A meta-analysis was performed using a fixed-effects model or a random-effects model, and effect sizes were reported as weighted mean differences or standardized mean differences. Results: Administration of rTMS significantly improved upper limb function, hand function, and muscle tone in stroke patients throughout the chronic phase [≥6 months], but not lower limb mobility and strength. In terms of cognitive function, rTMS has a considerable positive impact on patients' cognitive performance. rTMS also alleviated apathy in stroke patients more than post-stroke depressive symptoms regarding mental functioning. Balance and walking function, as well as functional activities of daily living, of patients were dramatically improved by rTMS. However, the current conclusions should be taken carefully due to the small sample size of the meta-analysis. Conclusions: This is the first meta-analysis of rTMS treatment in patients with chronic stroke to inform the selection of the optimal treatment strategy for patients with chronic stroke, which demonstrated that rTMS treatment has the potential to improve the effects of sequelae by improving upper limb function, hand function, and muscle tone. Keywords: Meta-analysis; rehabilitation; repetitive transcranial magnetic stimulation; sequelae; stroke.